PENGARUH LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN, KOMISARIS INDEPENDEN DAN CAPITAL INTENSITYTERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Anggita Wijaya Putri, 15.05.52.0188; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze and examine the effect of leverage, profitability, company size, independent commissioners and capital intensity on tax aggressiveness. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange (IDX).The sampling method uses purposive sampling with the research period from 2015 to 2017. The data processed is 217 companies. The testing technique uses multiple linear regression analysis. The results showed that leverage has a significant positive effect on tax aggressiveness, capital intensity has a positive and insignificant effect on tax aggressiveness, while profitability, company size and independent commissioners have a non-significant negative effect on tax aggressiveness.